Syntrichia laevipila Brid - Suarez, Guillermo Martin (2011)
As part of the "Mosses of Uruguay" project, specimens recently collected from Montevideo and Colonia (and deposited in LIL), were identified as Syntrichia laevipila, previously unknown from Uruguay. The Uruguayan Syntrichia laevipila is characterized by leaves spirally twisted when dry, suborbicular to spatulate, constricted in the middle, blunt, emarginated, unbordered, with plane margins; costa excurrent in a long, smooth, hyaline awn and with specialized asexual reproduction as propagula, which borne at the tip of stem and in axils of distal leaves. These propagula are elliptical or oval, multicellular, ecostate, papillose with 1-3 apical hyaline cells without papillae. In accordance with Gallego et al. (2005) this combination of characters are frequent in the called "morphotype B" which represent the typical S. pagorum.